UNDERSTANDING SALAFI THOUGHTS FROM DEBATES IN COMMUNITIES AND SOLUTIONS FOR THEIR SOLUTIONS - Hutagaluh, Oskar (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This study discusses the understanding of salafi religion and upheaval in the community so that there are conflicts in the community and find solutions in resolving these conflicts. Re-understanding the term salaf in classical literature, re-reading the historical development of "salafiyah" and discussing several matters closely related to salafiyah in its present form. Of course what is discussed in this study are those who call themselves salafi who are characterized by exclusivity, not all people and institutions that identify themselves with the salaf. The focus in this research is how to understand salafi religion? And what is the impact of understanding salafi like society and the solution for the solution? The method used in this research is a type of library research with a historical approach. The results of this study are looking at the course of history, salafiyah is not known as the name of a particular group that is used to distinguish the majority of Muslims from deviant groups. The name used, since the time of the Companions, as self-identification and as a differentiator from deviating schools is Ahl al-Sunnah wa al-Jamā'ah, with slight variations.